BLACK SITUATIONAL COMEDIES: A LEGACY OF STEREOTYPES, IDEOLOGY, AND HEGEMONY - Morgan, Donald (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2016)
The purpose of this essay is to outline re-occurring archetypes that are found within the confines of “Black Sitcoms”. This essay demonstrates how these archetypes perpetuate negative stereotypes about teenage, African American males, under the guise of comedy and entertainment. This is accomplished by introducing the two most utilized archetypes that represent the black, teenaged, male which are prevalent in black sitcoms, along with examples of said archetypes. In doing so, this article also demonstrates a dichotomy between these two character types, in an attempt to highlight disturbing acceptance of certain media narratives about the African American community. Furthermore, explanations are provided as to how each archetype preys upon negative stereotypes and sociological taboos within the African American community, which results in negative impacts on the social consciousness of the African American community. What is more, this essay examines the negative ideology and subsequent hegemony that these television shows produce. Finally, I conclude with my own thoughts, regarding these issues.Keywords:   African American, situational comedies, archetype, ideology, hegemony, stereotypes